2021
DOI: 10.1111/cns.13627
|View full text |Cite
|
Sign up to set email alerts
|

High‐sensitive clinical diagnostic method for PTPRZ1‐MET and the characteristic protein structure contributing to ligand‐independent MET activation

Abstract: Background PTPRZ1‐MET (ZM) is a critical genetic alteration driving the progression of lower‐grade glioma. Glioma patients harboring ZM could benefit from MET inhibitors. According to the remarkable role of ZM as a driver of glioma progression and indicator of MET inhibitor sensitivity, it is necessary to detect this alteration even when it presents in glioma with relatively fewer copies. Methods Herein, we proposed that ZM could be detected with a high‐sensitive method of reverse transcriptase PCR with 50 amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Kinase insert domain receptor fusion tumors showed very weak VEGFR2 expression, although VEGFR2 expression has been observed in synovial sarcoma and chordoma in patients with nonendothelial mesenchymal tumors [30]. Moreover, PTPRZ1-MET (P1, M2, P2, M2, P3, and M2) fusions were detected in tumors of the central nervous system [19], which covered almost the entire tyrosine kinase region, similar to the four tyrosine kinase fusions, VWC2-EGFR (V3; E2), ICK-KDR (I5; K2), FOXP2-MET (F2, M12), and CEP290-MET (C5, M12). A previous study showed there was ligand-independent phosphorylation of MET [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinase insert domain receptor fusion tumors showed very weak VEGFR2 expression, although VEGFR2 expression has been observed in synovial sarcoma and chordoma in patients with nonendothelial mesenchymal tumors [30]. Moreover, PTPRZ1-MET (P1, M2, P2, M2, P3, and M2) fusions were detected in tumors of the central nervous system [19], which covered almost the entire tyrosine kinase region, similar to the four tyrosine kinase fusions, VWC2-EGFR (V3; E2), ICK-KDR (I5; K2), FOXP2-MET (F2, M12), and CEP290-MET (C5, M12). A previous study showed there was ligand-independent phosphorylation of MET [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PTPRZ1-MET (P1, M2, P2, M2, P3, and M2) fusions were detected in tumors of the central nervous system [19], which covered almost the entire tyrosine kinase region, similar to the four tyrosine kinase fusions, VWC2-EGFR (V3; E2), ICK-KDR (I5; K2), FOXP2-MET (F2, M12), and CEP290-MET (C5, M12). A previous study showed there was ligand-independent phosphorylation of MET [19]. Overexpression of C- MET was observed in patients with FOXP2-MET and CEP290-MET .…”
Section: Discussionmentioning
confidence: 99%
“…[PMID:25853691 and PMID:34873473] ( Mallawaaratchy et al, 2015;Wei et al, 2021) Moreover, Wang Q. W et al (2021) suggested that the MET-STAT4-PD-L1 axis may act with tumor-associated macrophages to enhance immune escape in gliomas and cause poor prognosis in patients with GBM. And Huang et al (Huang R. et al, 2021) verified that PTPRZ1-MET (ZM) fusion was a key genetic change that drives the progression of low-grade glioma and helped ZM-carrying glioma patients benefit from MET inhibitors. In addition, the inhibition of receptor tyrosine kinases, including MET and/or its ligand hepatocyte growth factor (HGF), is a promising therapeutic strategy against tumor (Suzuki et al, 2010;Ge et al, 2013;Song et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…The mechanism of fusion acquisition is unknown. Studies on the PTPRZ1–MET fusion show that the MET TRK is constitutively activated resulting in its oncogenic properties [33]. Further, MET fusions are sometimes paired with MET exon 14 skip mutations; this exon promotes degradation of MET suggesting the deletion of this exon promotes gliomagenesis.…”
Section: Met Fusionsmentioning
confidence: 99%
“…This fusion transcript indicated a worse prognosis in these patients with overall survival being 239 days in fusion positive patients vs. 318 days in fusion-negative patients. This specific gene fusion was associated with patients age less than 40 years [33]. PTPRZ1–MET fusions have not been heavily studied in western populations.…”
Section: Met Fusionsmentioning
confidence: 99%